The method of determining the forces in the tendon apparatus of human fingers - S. P. Panchenko; A. O. Mametiev; L. Yu. Naumenko; S. A. Chernyshov; T. O. Zub (Сучасні медичні технології)
Being one of the most functionally loaded systems, the human hand and its anatomical structures are damaged quite often. Thus, injuries to the interphalangeal joints account for up to 60 % of all hand injuries. Post-traumatic arthrosis, contractures with persistent pain syndrome, stiffness and ankylosis of the joints are distinguished among the consequences of hand joint injuries. With the development of the endoprosthesis method, the use of which allows to restore the lost function of the organs of the musculoskeletal system, new opportunities are opening up in the rehabilitation of patients with various injuries of the joints of the hand.